Survey of attack and detection based on the full life cycle of APT - WANG Zhiwei; HE Xijie; YI Xin; LI Ziyang; CAO Xudong; YIN Tao; LI Shuhao; FU Anmin; ZHANG Yuqing (Tongxin xuebao)
The advanced persistent threat (APT) attack was explored from two perspectives: attack methods and detection methods. First, the definitions and characteristics of APT attacks were reviewed and the development of related attack models was summarized. Based on this, a more general APT full lifecycle model was proposed, which was divided into four stages: information gathering, intrusion execution, internal network penetration, and data exfiltration. For each stage, recent research papers from the past five years were thoroughly reviewed, and the attack and detection techniques for each stage were analyzed. Finally, in light of the dynamic landscape of APT attack and defense technologies, the paper underscores the formidable challenges confronting both offense and defense and offers guidance for future research in this domain.